Alâaddin Sâbit’s Unpublished Poems That Found in a Magazine - Akatay, Kübra; Şener, Hasan (Fırat University, 2021)
There are many literary works that are the source of our classical literature. One of them is undoubtedly anthology journals written in verse or prose. Although magazines reflect the literary taste of the author and the period in which they were written, they are important because they contain the poems of poets who do not have a divan, or poems of poets that are not in the crew councils or published divans of the poets who have a divan, and provide benefits to literary history researchers in many respects. In this study, after brief discussion about the magazines, general information about Mecmû'a-i Eş'âr and Fevâ'id, which is the subject of our research, will be given, then we will introduce the poetries of Bosnian Alaaddin Sabit, an important figure in our XVII. century literature, which is not included in his printed/ published divan, but recorded in the poetry magazines named Mecmû’a-i Eş’âr and Fevâid in the National Library with number 06 Mil Yz A 54.

Klasik edebiyatımıza kaynaklık eden pek çok edebî eser mevcuttur. Bunlardan biri de hiç şüphesiz manzum veya mensur olarak kaleme alınan antoloji niteliği taşıyan mecmualardır. Mecmualar, müellifinin ve yazıldığı devrin edebî zevkini yansıtmakla birlikte divanı olmayan şairlerin şiirlerini ya da divan sahibi olan şairlerin müretteb divanlarında veya neşredilmiş divanlarında bulunmayan şiirlerini bünyesinde barındırdığı için önem arz etmekte ve pek çok hususta edebiyat tarihi araştırmacılarına fayda sağlamaktadır. Bu çalışmada, mecmualardan bahsedildikten sonra Milli Kütüphane 06 Mil Yz A 54 numarada kayıtlı Mecmû’a-i Eş’âr ve Fevâ’id ile ilgili genel bilgiler verilecek, daha sonra XVII. yüzyıl edebiyatımızda önemli bir yer teşkil eden Bosnalı Alâaddin Sâbit’in bu mecmuada bulunan ve basılı/neşredilmiş divanında yer almayan şiirleri tanıtılacaktır.
ALÂADDİN SÂBİT’İN BİR MECMUADA TESPİT EDİLEN YAYIMLANMAMIŞ ŞİİRLERİ